Differential impact of post-deployment stress and PTSD on neural reactivity to emotional stimuli in Iraq and Afghanistan veterans. (January 2018) - DiGangi, Julia A.; Gorka, Stephanie; Afshar, Kaveh; Babione, Joseph M.; Schroth, Christopher; Greenstein, Justin E.; Proescher, Eric; Dolcos, Florin; Phan, K. Luan
Abstract: For many veterans returning from combat in Iraq and Afghanistan, the transition from military to civilian life is complicated by an array of postdeployment stressors. In addition to significant stress associated with reintegration after deployment, many returning veterans also contend with the added burden conferred by PTSD symptoms. While the relationship between PTSD symptoms and the neurobiological substrates of emotion dysregulation has begun to be studied, even less is known about the effects of postdeployment stress on neural function. In order to assess the relationship among a neural measure of attention to emotion (i.e. the late positive potential; LPP), PTSD symptoms and postdeployment stressors, EEG was recorded and examined in a linear mixed model of 81 OEF/OIF/OND veterans. Results revealed a main effect for postdeployment stressors such that increased postdeployment stress was associated with a relatively enhanced LPP across all emotion types. There was also a main effect for PTSD symptoms such that greater symptoms were related to a relatively blunted LPP across all emotion types. Findings may have important implications for understanding how both current stress and PTSD symptoms affect motivated attention as measured by the LPP. Moreover, this work highlights the need to consider the effects of current stress, in addition to PTSD symptoms, on the functioning of returning veterans.